Linking innovative work behavior with customer relationship management and marketing performance - Luminița Nicolescu; Alexandru Ioan Rîpa (Journal of Innovation & Knowledge (JIK), 2024)
Customer relationship management (CRM) plays an increasingly crucial role in ensuring organizational performance, including marketing results (MR), in today's highly dynamic and competitive business environment. Simultaneously, CRM can be influenced by various factors involving innovations in all fields. However, the linkage between innovative work behavior and CRM, along with its impact on MR, remains an unexplored area of interest in the academic and business worlds. This research aimed to analyze the relationship between the two forms of innovative work behavior (IWB) (individual and organizational IWB) and the dimensions of CRM (customer orientation, CRM organization, knowledge management, and technology-based CRM), as well as the consequential MR. The data collected from employees in Romania were analyzed using structural equation modeling methodology. The main findings revealed that individual IWB (IIWB) does not influence CRM dimensions, while organizational IWB (OIWB) positively impacts CRM. In other words, the collective capability to create and implement new ideas, complemented by organizational cultures and managers that support team innovative behaviors, positively influences the development of CRM dimensions rather than generating and promoting new ideas at an individual level. Additionally, the study reconfirmed that most CRM dimensions are positively linked to good MR and play a mediating role in the relationship between OIWB and MR. The effects of these discoveries suggest that companies should emphasize fostering OIWB to improve CRM and enhance their competitiveness.
Keywords: M19; M30; O39; 650; Innovative work behavior; Customer relationship management; Marketing results; Romania